PRINSIP PENGUTUSAN GEREJA ANTIOKHIA MENURUT KISAH PARA RASUL - Noh Ruku (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2018)
This research describes the principles of sending done by the church of Antioch in Acts and their relevance to the church nowadays The principles of sending executed by the church of Antioch in Acts can be traced in eight principles as follow: (1) HS as the Initiator, (2) solid leadership, (3) dynamic spirituality, (4) awareness of the guidance of the HS, (5) giving the best workers, (6) sending by regeneration of spiritual leaders, (7) partnership, (8) responsibility As writer, I recommend sending-church, missionaries and the support partners to use these principles for the continuity of sending missionaries until parousia.